2010
DOI: 10.1038/nrgastro.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Barrett esophagus: an update

Abstract: Many developments have been made in the field of Barrett esophagus that have tremendous clinical implications. There are new definitions of Barrett esophagus that have had an immediate clinical impact on cancer risk and screening. Of interest is the definition by the British Society of Gastroenterology, which does not require the presence of intestinal metaplasia for a diagnosis of Barrett esophagus. Imaging techniques that allow improved visualization of intestinal metaplasia at the cellular level are now bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 109 publications
0
23
0
1
Order By: Relevance
“…In mice the squamous epithelium extends into the dome of the stomach, pushing the boundary between stratified and columnar epithelia caudally, into the stomach (Figure 1). This boundary is important clinically because in humans it is the site of a precancerous condition known as Barrett’s metaplasia, wherein squamous tissue in the distal esophagus takes on the appearance and gene expression profile of intestine-type columnar cells (reviewed in [2]). Similar metaplasia often precedes cancer in the distal stomach but is rare elsewhere in the gut, suggesting that the esophagus-stomach boundary and diseased stomach epithelium retain an unusual degree of plasticity in fate.…”
Section: The Esophagus-stomach and Internal Gastric Boundariesmentioning
confidence: 99%
“…In mice the squamous epithelium extends into the dome of the stomach, pushing the boundary between stratified and columnar epithelia caudally, into the stomach (Figure 1). This boundary is important clinically because in humans it is the site of a precancerous condition known as Barrett’s metaplasia, wherein squamous tissue in the distal esophagus takes on the appearance and gene expression profile of intestine-type columnar cells (reviewed in [2]). Similar metaplasia often precedes cancer in the distal stomach but is rare elsewhere in the gut, suggesting that the esophagus-stomach boundary and diseased stomach epithelium retain an unusual degree of plasticity in fate.…”
Section: The Esophagus-stomach and Internal Gastric Boundariesmentioning
confidence: 99%
“…Several theories attempt to explain the cellular origins of Barrett's metaplasia: reflux mediated reprogramming of a resident squamous stem cell, stem cell migration from the gastric cardia in order to repopulate the damaged oesophageal mucosa or stem cells within submucosal ducts or glands regenerating the surface epithelium 6 7. A recent study gives precedence to the theory that Barrett's metaplasia arises from cells at the squamocolumnar junction (SCJ)8; in this study, p63 knockout mice were shown to develop a Barrett's-like metaplasia in the squamous fore-stomach, and retrograde growth of a population of Car4-expressing cells located at the SCJ was proposed as the origin of the metaplasia although no lineage tracing was performed.…”
Section: Introductionmentioning
confidence: 99%
“…15 Increased BMP4 expression has been observed in esophagitis and Barrett's esophagus where BMP4 induces the metaplastic transformation of squamous epithelial cells to columnar cells. 16 These examples indicate that BMP4 clearly has a specific role in various processes in adult tissues and organs although comprehensive data on this issue are currently lacking.…”
mentioning
confidence: 99%